Human rights - Duffel, Siegfried (My University, 2015)
"As I’m writing this, Christians are brutally murdering Muslims in the Central African Republic; people in Syria are being bombed, starved, and tortured; and homosexuals still face the death penalty in Iran as well as long prison sentences in countries like Uganda and Nigeria and persecution by thugs in many countries. These atrocities and many other disturbing phenomena are often called “human rights violations.” What gives them this status? That is a question about which there has been a surprising amount of disagreement among political philosophers."
Keywords: human rights